Riskhantering i stora anläggningsprojekt : En fallstudie av projekt Kiruna Ny Järnväg - Jonasson, Karin (2011)
Risk Management is an important competence, and one of the main subjects in research regarding Project Management. The Risk Management process consists of three basic steps: Risk identification, Risk analysis and evaluation and Risk treatment. Risk Management is of extra great importance in construction projects and projects that includes multiple organizations or contractors. This is due to the fact that uncertainty, in areas such as allocation of liability, communication, coordination and control, increases in projects with multiple parties. Formalized Risk Management processes are unusual and further research is needed to develop Best practice in Risk Management and to adapt methods within Project Management to different types of projects. The iron ore company, LKAB, has realized many and often large construction projects during a long period of time. Trafikverket (The Swedish traffic board) realizes countless numbers of projects every year, from small maintenance projects to large complex construction projects. In both organizations, it is common that projects include multiple contractors and external organizations, as in Kiruna Ny Järnväg (KNJ, Kiruna New Railway). This is a large construction project, whose main purpose is to build a new railway west of Kiruna city and the iron ore mine. The project is conducted in a joint project by LKAB and Trafikverket, where Trafikverket is the project owner, while LKAB is financing the whole project. KNJ is estimated to cost four billion Swedish kronor. Riskhandboken (the Risk Manual) has been compiled to ensure a well implemented Risk Management in KNJ. Riskhandboken describes how the Risk Management Process within KNJ should be conducted: from planning of the process, to descriptions of the Risk identification, analysis, evaluation, treatment and control. The purpose of the study is to examine how risk is managed in large construction projects, in theory and practice, to develop a suggestion for Best practice. The master thesis includes a literary review that has ...